'I just think it's dirty and lazy': Fat surveillance and erotic capital. (December 2016) - Winch, Alison
Contextualized within the UK mediascape, this article discusses how fat signifies the classed failures of neoliberalism. Because class aspiration, entrepreneurialism and the myth of the competitive individual are pivotal to the political economy of neoliberalism, fat is increasingly and vehemently vilified as abject across media platforms. Fat-surveillance media, which are marketed specifically to women by their visuals, gendered community, language and structures of feeling, participate in a 'gynaeopticon' where the controlling gaze is female, and the many women regulate the many women. Rather than being a top-down form of governance and discipline such as in the panopticon, control is affectively devolved among systems or networks of the policing gaze. As well as monitoring women along the lines of class, I argue that these media circumscribe the de-individualizing possibilities and passions of the libido.